Applied Accounting Theory: A Financial Reporting Perspective. - Burns, Thomas J.; Schatike, Rudolph W. (The Accounting Review, 1981)
Reviews the book "Applied Accounting Theory: A Financial Reporting Perspective," by Philip E. Meyer.